Actualization Of Islamic Education Values In - Nurhilaliyah (Journal of Global Educational Perspectives, 2026)
This article comprehensively discusses the implementation of Islamic educational values in science learning, which aims to achieve a harmonious integration between religious (naqli) and general (aqli) knowledge. The dichotomy that has separated science from the realm of values has contributed to a moral and ethical crisis in the utilization of science. This research aims to identify the concept of integrating Islamic values into science, relevant values that can be implemented, strategies and models for implementation, and the associated impacts and challenges. Using a qualitative approach with a literature review method, this article finds that integration is based on the monotheistic paradigm that views the universe as a sign of God's greatness (the kauniyah verses). Core values such as monotheism, caliphate, ihsan, contentment, and justice can be internalized through an integrated curriculum, relevant pedagogy (such as inquiry and value-based projects), and the role of teachers as role models. Positive impacts include character building, increased ethical awareness, and holistic understanding of students. However, challenges such as teacher capacity, curriculum resistance, and resource availability also need to be addressed. Successful implementation is expected to produce a generation that is not only scientifically competent but also possesses Islamic character and responsibility.